The memory jar [large type] - Goyer, Tricia (Goyer, Tricia. Seven brides for seven bachelors., 2013)
For the past ten years in the small Amish community of West Kootenai, Montana, Sarah Shelter has been passed over by the young Amish men that arrive there each year, until she meets Jathan Schrock.